1998
DOI: 10.1046/j.1365-2265.1998.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum collagen crosslinks as markers of bone turn‐over during GH replacement therapy in growth hormone deficient adults

Abstract: In summary, the present study confirms that administration of GH treatment to GHD adult patients significantly activates bone remodelling, with the effect of GH both in bone formation and bone resorption markers being maximal after 6 months of treatment. The serum assay for PYR and DPYR has a number of practical and theoretical advantages over the urine assay and gave similar results to those previously reported for the urine assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 42 publications
1
6
0
1
Order By: Relevance
“…The same trial reported a significant increase in peak handgrip strength in females while reporting insignificant changes or significant reductions in BMD/BMC (20). In two trials, the significant increases in muscle parameters occurred prior to the significant increases in bone parameters (17,18,37). In one trial, however, the increase in lumbar spine BMD was contemporary with the increase in muscle parameters (17).…”
Section: Effect Of Ghd and Gh Replacement On Both Muscles And Bonesmentioning
confidence: 90%
See 1 more Smart Citation
“…The same trial reported a significant increase in peak handgrip strength in females while reporting insignificant changes or significant reductions in BMD/BMC (20). In two trials, the significant increases in muscle parameters occurred prior to the significant increases in bone parameters (17,18,37). In one trial, however, the increase in lumbar spine BMD was contemporary with the increase in muscle parameters (17).…”
Section: Effect Of Ghd and Gh Replacement On Both Muscles And Bonesmentioning
confidence: 90%
“…Two trials reporting significant increases in muscle strength, also found significant increases in most, but not all, BMD and BMC values (18,21,37).…”
Section: Effect Of Ghd and Gh Replacement On Both Muscles And Bonesmentioning
confidence: 99%
“…It is difficult to speculate on the possible mechanisms involved in the process in vivo. The use of bone turnover markers is controversial (20)(21)(22). In fact, while in postmenopausal women, there is a correlation between bone turnover markers and BMD (23), in the same patients B-ALP and short-term changes in collagen cross-links during therapy are important predictive factors in bone mass recovery (23).…”
Section: Discussionmentioning
confidence: 99%
“…Estudos com uso de GH a longo prazo (pelo menos 18-24 meses) mostram aumento na DMO, mas ainda não se sabe se isso se traduz em uma redução no risco de fraturas (5,(49)(50)(51)(52)(53)(54). Encontramos aumento da DMO de coluna lombar e fêmur após 12 meses de reposição de GH (1,99±4,27% em coluna lombar e 2,55±4,30% no fêmur), que se manteve após 24 meses de tratamento (2,31±7,17% em coluna lombar e 5,33±9,64% no fêmur).…”
Section: Deficiência De Gh Em Adultos: Estudo Brasileirounclassified